Pelatihan Fiqih Praktis dan Menyenangkan bagi Mahasiswa Universitas Pendidikan Indonesia dengan Metode MUDAH Melalui Pendekatan MENARI: Practical and Enjoyable Fiqh Training for Students of Universitas Pendidikan Indonesia Using the MUDAH Method through the MENARI Approach - Abdullah, Mulyana; Faqihuddin, Achmad; Jenuri, Jenuri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Fiqh instruction in higher education often encounters challenges related to students' low levels of interest and understanding, particularly among those with general education backgrounds. The conceptual nature of fiqh content, when delivered through conventional methods, is frequently perceived as rigid and less relevant to the learning needs of today's generation. To address this issue, the Community Service Program (PkM) implemented the MUDAH Method through the MENARI Approach (Enjoyable, Educational, Structured verse, Active, Rhythmic, and Interactive) as an innovative model for practical fiqh training. The program aimed to enhance students' comprehension of fiqh in an enjoyable and applicable manner, while also equipping them with pedagogical skills relevant to their roles as future Islamic education teachers. The training was conducted intensively over two days and structured into five stages: preparation, orientation, interactive training, guided practice, and evaluation with reflection. The materials were delivered in rhythmic nadzam (verse) form, performed and practiced collaboratively. Evaluation results indicated significant positive outcomes, including a 92% improvement in comprehension, 95% active participation, and 96% overall satisfaction. The training also helped bridge the pedagogical gap between students from pesantren and non-pesantren backgrounds. In conclusion, the MENARI approach is proven to be an innovative, effective, and contextually appropriate strategy for teaching fiqh, offering substantial potential for broader application in Islamic higher education in Indonesia.